2018
DOI: 10.1111/eip.12770
|View full text |Cite
|
Sign up to set email alerts
|

Simulated long‐term outcomes of early use of long‐acting injectable antipsychotics in early schizophrenia

Abstract: Aim Duration of untreated psychosis in early schizophrenia impacts long‐term outcomes. Because long‐acting injectable (LAI) antipsychotic drugs improve adherence in early‐stage patients, they could reduce additional time in uncontrolled psychosis (TUP) during the critical period of the illness. However, the long‐term benefit of early LAI use over oral formulations has not been quantified. This study explores the potential magnitude of the benefit with a simulation approach. Methods A microsimulation models the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Given that inadequate medication adherence is common among patients with newly diagnosed schizophrenia, more active consideration of LAIs in this stage for better long-term outcomes should be encouraged, particularly for those who have already exhibited poor adherence attitudes. 39 , 37 , 45 , 46 , 47 , 48 Additional studies are also needed to clarify long-term adverse effects specific to LAIs use and identify specific psychotherapeutic and psychosocial interventions that may offer other benefits to patients in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Given that inadequate medication adherence is common among patients with newly diagnosed schizophrenia, more active consideration of LAIs in this stage for better long-term outcomes should be encouraged, particularly for those who have already exhibited poor adherence attitudes. 39 , 37 , 45 , 46 , 47 , 48 Additional studies are also needed to clarify long-term adverse effects specific to LAIs use and identify specific psychotherapeutic and psychosocial interventions that may offer other benefits to patients in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a 2016 survey of researchers and clinicians with LAI experience reported a strong consensus for prescribing LAIs not only to those who are nonadherent but also to patients with a broader range of conditions, such as certain histories (i.e., multiple hospitalizations/relapses, violence, suicide attempt, substance abuse), poor illness insight, cognitive impairment, and in patients aged 18-25 years [57]. Early introduction of LAIs can provide increased competitive employment/independent living and decreased disability/hospital admissions compared with OA treatment [58], supporting LAI use in a broader range of patients.…”
Section: Not Limited To Patients Who Are Nonadherentmentioning
confidence: 99%
“…One of the more frequent causes of relapse in schizophrenia is non-adherence (40). While the use of LAIs is often restricted to chronic patients with frequent relapses and poor adherence, some studies showed that LAIs may be effective also at the outset of schizophrenia (41,42) and there is a strong movement towards implementing LAI treatment early in the course of schizophrenia or other psychoses (43)(44)(45)(46). Furthermore, early treatment of FEP co-occurring with SUD was shown to benefit even patients with poor prognosis (47).…”
Section: Introductionmentioning
confidence: 99%